INTERPRETARIAT ÎNTRE PRACTIC Ă ŞI PROFESIE. - Cojocariu, Marinela (Studii de Ştiintă şi Cultură, 2009)
Against the background of the twentieth century professionalization of interpreting, with a particular regard to the increasing academization of training, the paper reviews several stages in the evolution of interpreting studies. Completing the theoretical cornerstones of inquiry it outlines the fundamental issues in methodology focusing on the deductive-vs.-inductive and quantitative-vs.- qualitative distinctions.